IMPLEMENTASI SISTEM PENDAFTARAN ONLINE DI RUMAH SAKIT UNTUK MENINGKATKAN EFISIENSI DAN KEPUASAN PASIEN - Lidya Paramitha Moha; Novitasari Ismail; Nininng Pakaya (Journal of Hulonthalo Service Society (JHSS), 2022)
The development of information technology is increasingly rapid and reaches various aspects of life, including in the health sector. The application of information technology in hospitals provides benefits in improving the efficiency and quality of health services, one of which is through an online registration system. This community service aims to provide information related to the online registration system that makes it easier for the public to access health services at hospitals. This service activity was carried out in East Pentadio village, Telaga Biru District, Gorontalo Regency. The method used is education and interactive discussions designed to provide an in-depth understanding of the online registration system to improve time efficiency and patient satisfaction. The results of the activity showed an increase in public understanding of the online registration system. This activity also identifies the main obstacles of society in the limitations of infrastructure and digital literacy and practical solutions to overcome them.